COMPETITION IN BRITISH RAILWAYS – WHAT HAVE WE LEARNED? - Preston, JOhn (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
In this paper I will try and draw some lessons for other countries from the experiences of railway reforms in Great Britain. In so doing, I will try and update the story in Changing Trains (Van de Velde, 1999, with a chapter on Great Britain by Root and Preston). I should start off with three important caveats. First, countries are different. In the project that led to the book Changing Trains, we tried to look at countries (or parts of countries) which were similar to The Netherlands. We concluded that there were no countries in the world similar to The Netherlands. We could equally have concluded that there are no countries similar to Great Britain. We could draw the same conclusion for Denmark. Secondly, what I am going to present is a personal, subjective view - some of which is backed up by empirical evidence, but some of which isn’t. What I want to do then is draw, somewhat randomly, 20 lessons from the British experience. I have been asked by the conference organisers to particularly try and present information on the degree of passenger satisfaction, the extent of ticket system co-ordination and the levels of investment. Thirdly, much of what I wish to say I have already said at the International Conference on Regulatory Reforms in the Railway Sector in Stockholm in July 1999. Apologies if you have heard this before.